Second language learning as a process of identity reconstruction: Bonnie Norton’s theory and the formation of L2 identity - Rakhmonov, Azizkhon Bositkhonovich (The Lingua Spectrum, 2026)
This article explores second language learning through the theoretical framework of B. Norton’s Identity Theory. In contrast to traditional language teaching approaches that conceptualize learning primarily as the acquisition of linguistic knowledge and communicative skills, the study adopts a sociocultural and psycholinguistic perspective, viewing second language learning as a complex process of personal and social transformation. The key theoretical construct of the research is L2 identity, defined as a set of psychological, cognitive, and sociocultural characteristics that emerge as individuals engage in communication through a second language. The article argues that a foreign language functions not only as a tool for communication but also as a symbolic resource through which learners reconstruct their self-concept, negotiate social roles, and develop new forms of subjectivity. Particular attention is paid to the dynamic and relational nature of identity, as well as to the role of power relations, social structures, and communicative experience in shaping the learner’s linguistic self. From a methodological perspective, the study emphasizes the need to shift the focus of language education from the transmission of linguistic knowledge to the design of identity-rich communicative practices, including narrative tasks, role-playing activities, and professional simulations. The article concludes that second language learning should be interpreted as an existentially meaningful process of identity reconstruction, in which linguistic competence and personal development are inseparable dimensions of a unified sociopsychological formation.